83PHelicobacter bilis may play a role in the carcinogenesis of colitis associated colon cancer correlating to increased number of CD4+CD45RB+ T cells. (24th November 2019) - Fu, X; Peng, W
Abstract: Background: The role of Helicobacter bilis (H.bilis) in the development of inflammatory bowel disease (IBD) and colitis-associated carcinogenesis (CAC) has seldom been investigated. Methods: Using 16S rRNA fluorescence in situ hybridization (FISH), we examined the abundance of H.bilis in 58 colorectal cancers (CRCs), 20 IBDs, 40 normal colorectal mucosae (NCs) and 20 adenomas (ADs). Number of CD4 + CD45RB + T cell and expression of IFN-γ and TNF-α in these tissues was determined by immunofluorescence. Results: The abundance of H.bilis was significantly higher in CRCs (33.7±27.7) than that in IBDs (15.0±16.3; P = 0.006), ADs (4.01±7.3; P < 0.001) and NCs (1.1±3.0; P < 0.0001). The abundance of H.bilis in IBDs was significantly higher than that in ADs (P = 0.013). Moreover, the average number of CD4 + CD45RB + T cell was significantly higher in CRCs (5.7±3.2) than that in IBDs (1.9±1.8, P = 0.013) and NCs (1.0±1.0, P = 0.008). In addition, there was a positive correlation between the H.bilis abundance and density of CD4 + CD45RB + T cells in 30 colorectal tissues (including 19 CRCs, 6 IBDs and 5 NCs) (Spearman correlation coefficients 0.6625, 95%CI 0.3875-0.8292, P < 0.0001). The frequency of co-staining for CD4 + CD45RB + T cells and IFN-γ was significantly higher in H.bilis positive group (including 5 CRCs and 4 IBDs)than that in H.bilis negative group (including 5 CRCs and 4 IBDs) (P = 0.002). Conclusions: H.bilis may play a role in the initiation of IBD and CAC, possibly through promoting the transformation of T cells into CD4 + CD45RB + T cells and increasing the expression of proinflammatory cytokines IFN-γ. Legal entity responsible for the study: Xiangsheng Fu. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.